Measuring Institutional Quality in Argentina: The Devil Is in the Details - Reisberg, Liz (International Higher Education, 2008)
More than a decade after launching a national quality assurance program, Argentina may be pursuing a worthy cause on the wrong path. The country has adopted schemes in use elsewhere without accommodating conditions that make higher education in Argentina very different. Measuring itself by the evaluation criteria applied elsewhere, Argentine universities are diverting attention and resources from improving their primary activityteaching.